Efficiency of Optimized Technology of Switchgrass Biomass Production for Biofuel Processing - KULYK, Maksym; KURILO, Vasyl; PRYSHLIAK, Natalia; PRYSHLIAK, Viktor (Journal of Environmental Management and Tourism; Vol 11 No 1 (2020): JEMT Volume XI Issue 1(41) Spring 2020DO - 10.14505//jemt.v11.1(41).20, 2020)
In order to reduce the dependence on fossil energy sources in Ukraine, the need to develop its own alternative energy fuels production has arisen. Switchgrass is used in many countries as an efficient energy non-food crop for biofuel production. The main methods to use switchgrass for energy purposes is the production of electricity through gasification, combined combustion and the production of second-generation biofuels. Due to the relevance of the energy security problem in Ukraine, the need to develop an optimized switchgrass growing technology is substantiated in the article. The energy efficiency of optimized cultivation technology based on calculated indicators has been established. The impact of conditions and cultivation techniques on yield of switchgrass has been investigated. The effects of optimized growing technology and growing conditions on the energy efficiency of switchgrass biomass production have been studied. The energy output and energy efficiency coefficient, depending on the technology of growing switchgrass has been established. The results of long-term studies show an increase in the yield of this crop (at a level or above 15.0 t / ha), depending on the elements of the cultivation technology and growing conditions.